Object-oriented system development - Champeaux, Dennis de (Addison-Wesley, 1993)
Rather than subscribing to a particular object-oriented method, the authors give instructions on how to put key object-oriented concepts to work in software construction. Many examples, including a full banking system, are developed throughout the book to illustrate the process of object-oriented so.